Latent class analysis and profiles of teaching quality in higher education in Ecuador - González-Berruga, Manuel (2026)
Ecuadorian students face difficulties and barriers in their transition through university. A lack of adaptation to university processes or difficulties in meeting course content and competency requirements, among other factors, may place them in a situation of academic risk, leading to experiences of failure and dropping out. Latent Class Analysis is a statistical technique that makes it possible to characterize academic risk profiles within the university context. Within this framework, the objective was to identify possible academic risk profiles based on perceptions of teaching quality and perceptions of adaptation to university, using Latent Class Analysis. The study followed a quantitative approach with an exploratory–descriptive scope, employing Latent Class Analysis (LCA) as the method of analysis. Data were collected at PUCE Esmeraldas (Ecuador) from N=208 students using the Student Course Experience Questionnaire and from N=124 students using the Student Perceived Fit Questionnaire. The results yielded four classes for the SCEQ: very high academic risk (Class 1), medium academic risk (Class 2), very low academic risk (Class 3), and low risk (Class 4); and two classes for the SPFQ: low risk associated with adequate adaptation to university (Class 2) and a risk profile associated with a lack of adaptation to university (Class 1). Consequently, measures should be proposed aimed at comprehensive assessments that enable individualized monitoring of university students’ trajectories.